In Situ Direct Laser Writing of 3D Graphene‐Laden Microstructures. Issue 8 (19th June 2021) - Restaino, Michael; Eckman, Noah; Alsharhan, Abdullah T.; Lamont, Andrew C.; Anderson, Jackson; Weinstein, Dana; Hall, Asha; Sochol, Ryan D.
Abstract: A wide range of applications rely on the ability to integrate electrically conductive microstructures with microfluidic channels. To bypass the planar geometric restrictions of conventional microfabrication processes, researchers have recently explored the use of "Direct Laser Writing (DLW)"—a submicron‐scale additive manufacturing (or "3D printing") technology—for creating conductive microfeatures with fully 3D configurations. Despite considerable progress in the development of DLW‐compatible photomaterials, thermal post‐processing requirements to support electrical conductivity remain a critical barrier to microfluidics integration. In this work, novel graphene‐laden photocomposites are investigated to enable DLW‐based printing of true 3D conductive microstructures directly inside of enclosed microchannels (i.e., in situ). Photoreactive composite materials comprising reduced graphene oxide (rGO) particle concentrations of up to 10 wt% exhibited high compatibility with DLW, with minimal optical interference at critical wavelengths. Developed rGO‐photocomposites revealed an ultimate DC conductivity of 9.85 ± 0.48 × 10 −5 S m −1 . Experimental results for DLW of 3D microcoils (1 wt% rGO; wire diameter = 10 µm; coil diameter = 40 µm) revealed an impedance of 2.71 ± 0.12 MΩ at 2 MHz. In addition, results for in situ DLW of geometrically sophisticated rGO‐laden microstructures suggest utility of the presented approach for potential 3D microelectronics‐based microfluidic applications. Abstract : The submicron‐scale additive manufacturing strategy, Direct Laser Writing (DLW), is employed as a means to circumvent the intrinsic geometric restrictions of conventional microfabrication processes. A DLW‐compatible, graphene‐laden photocomposite is developed and investigated for 3D printing embedded conductive microstructures directly inside enclosed microfluidic devices. In this work, the fabrication and performance of the DLW fabricated graphene‐laden microstructures are explored.